مصطفى إبن حليم ودوره في دعم الثورة الجزائرية - زعبان أسماء; د/ جفال عمر (My University, 2023)
الملخص: لقد عرفت العلاقات الجزائرية الليبية خلال الثورة الجزائرية 1954-1962م تطورات هامة على جميع الأصعدة ويتضح هذا من خلال شخصية رئيس الحكومة الليبية مصطفى إبن حليم وموقفه من الثورة الجزائرية وذلك من خلال تقديمة لمختلف أشكال الدعم للثورة الجزائرية خاصة خلالمرحلة ترأسه للحكومة الليبية 1954-1958م سواء كان على المستوى السياسي أو العسكري أو الإجتماعي، وذلك رغم محاولات السياسة الفرنسية إتجاه الحكومة الليبية من أجل وقف الدعم والإمداد عن الثورة الجزائرية بمختلف أشكاله. Summary: During the Algerian revolution 1954-1962 AD, the Algerian-Libyan relations witnessed important developments at all levels, and this is evidenced by the head of government, Mustapha Ibn Halim, and his position in support of the Algerian revolution, through his provision of various forms of support for the Algerian revolution, especially during the period he headed the Libyan government 1954- 1958 AD, whether on the political, military or social level, despite the attempts of French policy towards the Libyan government in order to stop support and supply for the Algerian revolution in its various forms.